Output position and word relatedness effects in a DRM paradigm: Support for a dual-retrieval process theory of free recall and false memories - Barnhardt, Terrence M.; Choi, Hyun; Gerkens, David R.; Smith, Steven M. (Journal of memory and language, 2006)
Five experiments investigated predictions—derived from a dual-retrieval process approach to free recall (Brainerd, C. J., Wright, R., Reyna, V. F., & Payne, D. G. (2002). Dual-retrieval processes in free and associative recall. Journal of Memory and Language, 46, 120–152.)—about false memories in a DRM-like paradigm. In all the experiments, the presence of the critical words in the study lists was manipulated within subjects. In all the experiments, the output position of presented critical words was earlier than the output position of nonpresented critical words and the output positions of both types of words was closer to the center than to the ends of the recall protocols. In Experiments 2–5, unrelated words were intermixed with related words in the study lists. In all of these experiments, recall of related words was greater than recall of unrelated words. However, in Experiments 4 and 5, the advantage for recall of related words was greater after the critical item was output than before it was output. These findings were consistent with the notions that: (1) there are two successive retrieval processes (direct access of verbatim traces and reconstruction from gist traces) in free recall, (2) items are recalled in ascending order of strength during direct access and descending order of strength during reconstruction from gist, and (3) false memories for words are attributable to reconstruction from gist traces.